A Study on the Relationship Between Consumer Motivations and Subjective Well-Being: A Latent Profile Analysis - Xiao, Jun; Gong, Yanping; Li, Jian; Tang, Xiuyuan; Javeed, Sohail Ahmad; Deng, Yuling (Frontiers in Psychology, 2022)
Consumer motivation performs an important role in their purchase decision and well-being. Previous studies have investigated the relationship between certain consumer motivation and well-being separately. We aim to employ latent profile analysis (LPA) to explore subgroups of participants who display similar patterns of consumer multiple motivations and to examine differences in subjective well-being across these sub-types. Participants (N =1023, ages 18-58) completed the Consumer Motivation scale online to assess seven dimensions of consumer motivation. Results of LPA identified that four subpopulations of participants: the enthusiastic group has high expectations in all aspects; the balanced group values each aspect of the product, but has lower expectations; the rational group emphasizes aspects such as value for money, comfort, and quality; the apathetic group has no strong motivation for consumption, and they are relatively concerned with the dimensions of security, social acceptance, and stimulation. Consumers subjective well-being (life satisfaction, positive affect, and negative affect) differed significantly across the four profiles. Specifically, scores for positive affect and life satisfaction were highest in the enthusiastic group, medium in the balanced group, and lowest in the rational and apathetic groups. Scores for negative affect were significantly higher in the enthusiastic and apathetic groups than in the rational group. These findings enable marketers to develop customized marketing strategies for different motivation profiles and contribute to consumers with varying motivation profiles to consciously pay attention to their well-being.